Peningkatan Disiplin Guru SD Melalui Pelatihan Partisipatif Model In-On - Slameto Slameto; Agustina Tyas Asri Hardini; Tego Prasetyo; Endang Indarini (Kelola: Jurnal Manajemen Pendidikan, 2018)
This research is taken place to describe the punctual improvement of the teacher who’s participated in participatory training model using in-on and to determine the influence of teacher optimism and teacher's ability to give feedback, along with the contribution of each variable. This research was conducted based on the assessment of elementary school teachers who are participated in training for classroom action research preparation in KKG Gugus Joko Tingkir Salatiga, with 42 selected people randomly. Data for this research is quantitative. Data were collected through a self-rating scale of 21 items that proved to be valid and reliable. Data analysis using multiple linear regression with Stepwise Model. Based on the result of this research, it can be proved participatory training model effective in improving teacher’s punctual in teaching. There are 2 variables/predictors of teacher optimism and or together with their ability to provide feedback on teacher’s punctual in teaching. Teacher's optimism has an effect (positive and significant) on teacher’s punctual in teaching equal to 35.20%. Teacher’s optimism along with their ability to give feedback impact teacher’s punctual in teaching as much as 42.9%. Thus participatory training model should be applying learning principles that emphasize positive optimistic psychology, get used to working effectively with challenges, have the confidence to use innovative thinking in achieving success.